Problematika Kebocoran Data Pribadi Akibat Publikasi Data Pribadi dalam Arsip Direktori Putusan pada Situs Mahkamah Agung Ditinjau dari Perspektif Undang-Undang Nomor 27 Tahun 2022 tentang Perlindungan Data Pribadi - Firstnandiar Glica Aini Suniaprily; Muhammad Aziz Zaelani; Adhy Nugraha (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The loss of personal data is a serious problem that is becoming more frequent, especially in relation to the publication of data on official websites such as the Supreme Court. This review addresses the issue of loss of personal data due to publication to the Decree Directory Archive in light of Law No. 27 of 2022 on Personal Data Protection (PDP). The purpose of this study is to analyze how Law No. 27 of 2022 can address the problem of loss of personal data arising from publication on the Supreme Court website. By understanding the existing regulations, it is hoped that a solution can be found to strengthen personal data protection in Indonesia. The approach used is prescriptive and legal, with analysis of current regulations and past data breach cases. Secondary data from legal literature and incident reports are analyzed to provide a comprehensive picture of the problem. All parties involved should take serious precautions against data leaks caused by postings on official websites such as the Supreme Court. To prevent similar incidents in the future, it is necessary to strengthen regulations through Law No. 27 of 2022 and raise awareness of the importance of personal data protection.